Expression of Oligodendrocyte and Oligoprogenitor Cell Proteins in Frontal Cortical White and Gray Matter: Impact of Adolescent Development and Ethanol Exposure - Liu, Wen; Rohlman, Aaron R.; Vetreno, Ryan; Crews, Fulton T. (Frontiers in Pharmacology, 2021)
Adolescent development of prefrontal cortex (PFC) parallels maturation of executive functions as well as increasing white matter and myelination. Studies using MRI and other methods find that PFC white matter increases across adolescence into adulthood in both humans and rodents. Adolescent binge drinking is common and has been found to alter adult behaviors and PFC functions. This study examines development of oligoprogenitor (OPC) and oligodendrocytes (OLs) in Wistar rats from adolescence to adulthood within PFC white matter, corpus callosum forceps minor (fmi), PFC grey matter and the neurogenic subventricular zone (SVZ) using immunohistochemistry for marker proteins. In addition, the effects of adolescent intermittent ethanol exposure (AIE; 5.0 g/kg/day, intragastric, 2 days on/2 days off on postnatal day [P]25-54), which is a weekend binge drinking model, were determined. OPC markers NG2, PDGFR and Olig2+IHC were differentially impacted by both age and PFC region. In both fmi and SVZ, NG2+IHC cells declined from adolescence to adulthood with AIE increasing adult NG2+IHC cells and their association with microglial marker Iba1. PFC grey matter decline in NG2+IHC in adulthood was not altered by AIE. Both adult maturation and AIE impacted OL expression of MBP, PLP, MAG, MOG, CNPase, Olig1, and Olig2 in all three PFC regions, but in region- and marker-specific patterns. These findings are consistent with PFC region-specific changes in OPC and OL markers from adolescence to adulthood as well as following AIE that could contribute to lasting changes in PFC function.